Bibliometric insights into astrocytic roles in depression and treatment - Linsun Lin; Linsun Lin; Ziyi Guo; Zhuoyu Ren; Yanchen Feng; Peigang Fang; Tao Wang; Min Chen; Min Chen (Frontiers in Cellular Neuroscience)
ObjectiveDepression is a mental disorder that significantly impairs both physical and mental health. Recent studies have shown that reactive astrogliosis have gained significant attention for their involvement in the pathophysiology of depression. However, there is no bibliometric analysis in this research field. This study aims to provide a comprehensive overview of the knowledge structure and research hotspots regarding the role of astrocytes in the mechanisms and treatment of depression through bibliometric analysis. The scope of the literature review encompasses both basic and clinical research.MethodsPublications related to astrocytes in depression and treatment from 2014 to 2023 were searched in the Web of Science Core Collection (WoSCC) database. VOSviewer, CiteSpace, and the R package “bibliometrix” were used to conduct this bibliometric analysis.ResultsFrom 2014 to 2023, a total of 1,502 documents from 78 countries on astrocytes in depression and treatment were analyzed from 169 journals, with the most co-cited journals being the Journal of Neuroscience and PNAS. China Medical University was the most productive institution. The analysis identified key authors like Verkhratsky Alexei and Baoman Li, and major co-cited references by Rajkowska and Liddelow. Keywords such as “synaptic plasticity,” “astrocytes,” and “neuroinflammation” revealed research trends focusing on molecular mechanisms, gut microbiota, and inflammation.ConclusionThis is the first bibliometric study to comprehensively summarize the research trends and advancements regarding astrocytes in depression and its treatment. Through this bibliometric analysis, we aim to enhance the understanding of the significance of astrocytes in depression research and provide new perspectives and insights for future investigations. We hope that this study will facilitate a broader integration of basic and clinical research, offering novel approaches for the treatment of depression.